The power of cities
1 online resource.
Keywords: The Power of Cities focuses on Iberian cities during the lengthy transition from the late Roman to the early modern period, with a particular interest in the change from early Christianity to the Islamic period, and on to the restoration of Christianity. Drawing on case studies from cities such as Toledo, Cordoba, and Seville, it collects for the first time recent research in urban studies using both archaeological and historical sources. Against the common portrayal of these cities characterized by discontinuities due to decadence, decline and invasions, it is instead continuity – that is, a gradual transformation – which emerges as the defining characteristic. The volume argues for a fresh interpretation of Iberian cities across this period, seen as a continuum of structural changes across time, and proposes a new history of the Iberian Peninsula, written from the perspective of the cities. Contributors are Javier Arce, María Asenjo González, Antonio Irigoyen López, Alberto León Muñoz, Matthias Maser, Sabine Panzram, Gisela Ripoll, Torsten dos Santos Arnold, Isabel Toral-Niehoff, Fernando Valdés Fernández, and Klaus Weber.